Originally Posted by
Soroban Hello, arslan!
We are expected to know the formula:
. . $\displaystyle P(A \cup B) \;=\; P(A) + P(B) - P(A \cap B)$
Let $\displaystyle S$ = faulty switch, $\displaystyle C$ = faulty cord.
We are told that: .$\displaystyle \begin{array}{ccc}P(S \cup C) &=& 0.06 \\ P(S) &=& 0.024 \\ P(S \cap C) &=& 0.03 \end{array}$
We have: .$\displaystyle P(S \cup C) \;=\;P(S) + P(C) - P(S \cap C) $
. . . . . . . . . .$\displaystyle 0.06 \;\;\;= \;\;0.024 + P(C) \;\;-\;\; 0.03$
Therefore: .$\displaystyle P(C) \:=\:0.066$